Prognostic role of euthyroid sick syndrome in MIS-C: results from a single-center observational study - Fastiggi, Michele; Meneghel, Alessandra; Gutierrez de Rubalcava Doblas, Joaquin; Vittadello, Fabio; Tirelli, Francesca; Zulian, Francesco; Martini, Giorgia (Frontiers in Pediatrics, 2023)
Background: Euthyroid sick syndrome (ESS) is characterized by low serum levels of free triiodothyronine (fT3) with normal or low levels of thyroid stimulating hormone (TSH) and free thyroxine (fT4) and is reported in different acute clinical situations, such as sepsis, diabetic ketoacidosis and after cardiac surgery.Our aim was to evaluate the predicting role of ESS for disease severity in patients with Multisystem Inflammatory Syndrome in children (MIS-C).: A single-centre observational study on consecutive patients with MIS-C. Before treatment clinical, and laboratory data were collected and, in a subset of patients, thyroid function tests were repeated 4 weeks later. Variables distribution was analyzed by Mann-Whitney U test and correlations between different parameters were calculated by Spearman's Rho coefficient. Results: Forty-two patients were included and 36 (85.7%) presented ESS. fT3 values were significantly lower in patients requiring intensive care, a strong direct correlation was shown between fT3 and Hb, platelet count and ejection fraction values. A significant inverse correlation was retrieved between fT3 levels and Creactive protein, brain natriuretic peptide, IL-2 soluble receptor and S-100 protein. Subjects with severe myocardial depression (EF < 45%) had lower fT3 values than subjects with higher EF. The thyroid function tests spontaneously normalized in all subjects who repeated measurement 4 weeks after admission. Conclusion: ESS is a frequent and transient condition in acute phase of MIS-C. A severe reduction of fT3 must be considered as important prognostic factor for severe disease course, with subsequent relevant clinical impact in the management of these patients.